2017
DOI: 10.1044/2016_jslhr-l-15-0334
|View full text |Cite
|
Sign up to set email alerts
|

Research to Establish the Validity, Reliability, and Clinical Utility of a Comprehensive Language Assessment of Mandarin

Abstract: DREAM holds promise as a diagnostic test of Mandarin language impairment for children aged 2;6 to 7;11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The test provides four component scores: receptive language, expressive language, syntax, and semantics. As reported by Liu et al (2017), test-retest reliability was high (r = .85). External validity was assessed using spontaneous language indices (e.g., sentence complexity, vocabulary diversity) and narrative indices (e.g., the inclusion of mental verbs and connectives).…”
Section: Methodssupporting
confidence: 61%
See 4 more Smart Citations
“…The test provides four component scores: receptive language, expressive language, syntax, and semantics. As reported by Liu et al (2017), test-retest reliability was high (r = .85). External validity was assessed using spontaneous language indices (e.g., sentence complexity, vocabulary diversity) and narrative indices (e.g., the inclusion of mental verbs and connectives).…”
Section: Methodssupporting
confidence: 61%
“…We used a cutoff score of 80 on any of the DREAM components as one of our inclusionary criteria. According to Liu et al (2017), the DREAM demonstrated the best sensitivity (73%) and specificity (82%) using this criterion (< 80 on one component) when measured against a priori 2 MENT © 2014 by Bethel Hearing and Speaking Training Center Inc. 3 Different IQ cutoff scores have been adopted by researchers (Gallinat & Spaulding, 2014). In our sample, five children with LI scored from 70 to 79.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations